PERAN KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA REPUBLIK INDONESIA DALAM MENGIMPLEMENTASIKAN UNDANG-UNDANG NOMOR 16 TAHUN 2011 TENTANG BANTUAN HUKUM - Umi Laili (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
The State guarantees the right of every person constitutional for recognition, security, protection and fair legal certainty and equal treatment before the law as a means of protection of human rights. Provision of legal aid to the poor as the realization of access to justice is the responsibility of the state.Ideally someone who is able (the have) that have a legal problem and someone who are poor (the have not) who also have a legal problem, all have defense of the right to request a public defender or as workers in legal aid for defend their interests in a lawsuit.This condition must be met in order in order to realize the principle of equality before the law and equal access to justice and behavior (acces to justice). In fact, a number of humanitarian cases invite the attention of the public, which shows the lack of access of the poor to obtain legal aid. This study aims to describe the implementation model of legal aid for the poor in the field, which is implemented by the Ministry of Justice and Human Rights of the Republic of Indonesia.This research uses quantitative research, where the primary data from informants from the ministry of law and human rights, legal aid and academics from university. While secondary data from literature from books, scientific manuscripts, research reports, and documents related to the research topic.